PENGARUH PENDIDIKAN, PELATIHAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PENYULUH KELUARGA BERENCANA - Doane Doane; Aidin Hudani Awasinombu; Asrip Putera (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
The purpose of this research is: 1) to know the influence of education on the performance of family planning extension in Wakatobi District; 2) to know the effect of training on the performance of family planning extension in Wakatobi District; 3) to know the impact of the working environment on the performance of the family planning extension in Wakatobi District; and 4) to determine the impact of education, training, and work environment simultaneously on the performance of the family planning extension in Wakatobi District. This research is categorized as research survey, where the research instrument is a questionnaire. The population in this study is the entire KB extension at DPKKB in Wakatobi Regency which amounted to 30 employees with the determination of the census samples. Data analysis In this study used multiple linear regression analyses using SPSS software. The results showed that : 1) education was significant and in direct response to the extension performance at the District DPKKB Wakatobi; 2) the training is significant and is in direct response to the extension performance at DPKKB, Wakatobi regency; and 3) the working environment is significant and is in direct direction to the extension performance at DPKKB District Wakatobi. Keywords: education, training, work environment and employee performance